Preserving the self with artificial intelligence using VIPCare—a virtual interaction program for dementia caregivers - Francis, Linda; Ghafurian, Moojan (Frontiers in Sociology, 2024)
Assistive technology is increasingly used to support the physical needs of differently abled persons but has yet to make inroads on support for cognitive or psychological issues. This gap is an opportunity to address another-the lack of contribution from theoretical social science that can provide insights into problems that cannot be seen. Using Affect Control Theory (ACT), the current project seeks to close that gap with an artificially intelligent application to improve interaction and affect among people with Alzheimer's Disease and Related Dementias (ADRD).Persons with ADRD forget details of their lives, making it difficult for them to interact with others. However, those who have lost cognitive memory appear to retain their established selfsentiments; they still feel like themselves and continue to act and react on that basis. This study uses sociological theory to model interactions with persons with ADRD based on that persons' self-sentiments, rather than cognitive memory, which inform a cellphone-based assistive tool called VIPCare for supporting caregivers. Staff focus groups and interviews with family members of persons with ADRD in a long-term residential care facility collected residents' daily needs and personal histories. Using the evaluation, potency, and activity dimensions of ACT, researchers used this information to formulate a self-sentiment profile for each resident and programmed that profile into the VIPCare application. VIPCare used that profile to simulate affectively intelligent social interactions with each unique resident that reduce deflection from established sentiments and, thus, negative emotions. We report on the data collection to design the application, develop self-sentiment profiles for the resident, and generate assistive technology that applies a sociological theory of affect to real world management of interaction, emotion, and mental health.